ANALISIS KUALITAS APLIKASI UJIAN ONLINE BERBASIS WEB PADA PERUM PERUMNAS - Hoga Saragih; Siti Safarina (Jurnal Sistem Informasi, 2014)
Human Resources Department utilizing information and communication technology development to further improve the quality of the company's employees. One of them by developing a Web-Based Employee Application Exam. Department of Human Resources at Housing realize that the role of employees determine the success or failure of the company to achieve its objectives. With a good selection implementation process, employees received will be qualified so that coaching, development, and setting employees becomes easier. This research will evaluate the quality of a website online exam based on the Web-site Quality Evaluation Method. The results of the analysis indicate that website quality is not satisfactory, so the need for design development of a prototype website using the Spiral Development Method.